Design of Islamic Religious Education Curriculum Strategy for Strengthening Teenagers' Moral Resilience in the Digital Era - Kamila Azzahra; Latif Al Ashar; Nurul Mubin (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
This research is motivated by the phenomenon of the adolescent moral crisis in the digital era, which has become increasingly concerning, evidenced by a loss of etiquette (adab) and character degradation within cyber spaces. This condition poses a significant challenge for educational institutions, particularly boarding schools, where restricted technological access often triggers an explosion of immoral behavior once students regain digital freedom. This study aims to formulate the concept of moral resilience from the perspective of Islamic Education (PAI) as a strategy for strengthening student character. The method employed is qualitative research with a literature study approach and content analysis. The findings indicate that moral resilience in Islamic Education is rooted in three main pillars: Istiqamah (consistency/steadfastness), Izzah (self-dignity), and Muraqabah (mindfulness of Divine supervision). These three pillars are integrated into a strategic curriculum design through moral reasoning-based learning and authentic evaluation models. This study concludes that strengthening moral resilience is capable of transforming external compliance into solid internal control, ensuring that adolescents maintain moral integrity even when navigating the boundless digital environment.